PRAKTEK PEMBUATAN DAN SIMULASI ROBOT LINE FOLLOWER UNTUK MENINGKATKAN MINAT BELAJAR SISWA BIDANG IPA DI RUMAH PADA SMPN 6 SELUMA - Afrizal Mayub; M Luthfi Firdaus; Henny Johan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Community Service is an activity that must be carried out by every Lecturer, therefore Lecturers for S2 Natural Science FKIP Bengkulu University collaborated with the Science Subject Teacher Conference (MGMT) of Seluma District Middle School / MTs dated 24 May 2019 for Community Service activities at SMPN 6. Collaboration It was followed up with community service activities at SMP N 6 Seluma with the title "The Practice of Making and Simulating Line Follower Robot to Increase Student Interest in Science at Home at SMPN 6 Seluma". From these activities it can be concluded that; The school will prepare a simple electronics / robotics laboratory at SMP N 6 Seluma by utilizing unused electronic equipment, it can be seen that the motivation of science teachers to apply robotics skills in school activities, students' interest and motivation towards robotics skills is very good.